2018
DOI: 10.3991/ijim.v12i2.7679
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Teacher Candidates on the Usage of Mobile Applications in the Multimedia Development Processes

Abstract: Abstract-In order for mobile applications to be employed successfully in education, the opinions of teachers on the use of these applications must be identified and improved. For this reason, the purpose of this study is to identify the opinions of teacher candidates, who are the teachers of the future, on the usage of mobile applications in the process of multimedia project development. This study, which was conducted with the purpose of identifying the opinions of teacher candidates on the usage of mobile ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Here MDCA succeed to make a big move in web technologies rendering them as more creative and attractive, [22], through a philosophy to maximize collective intelligence among a group of users which added value to every user participating with a dynamic information [23]. Mobile social applications are tools that provide unique opportunities to socially exchange all kinds of information and multimedia through synchronous and asynchronous communications that encourage interaction and sharing of different knowledge production [24,25]. This means that MDCA are comprehensive services in which people interact usin their mobile devices, and however allows learner to share activities and interests, make friends, and look for interests and activities adopted by other learners.…”
Section: Mobile Digital Content Applications (Mdca)mentioning
confidence: 99%
See 1 more Smart Citation
“…Here MDCA succeed to make a big move in web technologies rendering them as more creative and attractive, [22], through a philosophy to maximize collective intelligence among a group of users which added value to every user participating with a dynamic information [23]. Mobile social applications are tools that provide unique opportunities to socially exchange all kinds of information and multimedia through synchronous and asynchronous communications that encourage interaction and sharing of different knowledge production [24,25]. This means that MDCA are comprehensive services in which people interact usin their mobile devices, and however allows learner to share activities and interests, make friends, and look for interests and activities adopted by other learners.…”
Section: Mobile Digital Content Applications (Mdca)mentioning
confidence: 99%
“…People who perform activities due to external incentives, once removed, they become less willing to perform learning tasks and activities [5][6][7]. However, some research studies that aimed at analyzing performances and tasks implementation that are stimulated by external incentives as compared to those not stimulated by any incentives have shown that the effectiveness of the performance and task implementation is in favor of the group that was supported by incentives, as indicated by study [8] that examined 12 different studies which aimed at running (25) comparisons; these comparisons included incentive assisted performance vs performances that did not receive any incentive at all. The results have shown an effect degree of (0.6) in favor of groups that obtained additional external incentives, which means that it is difficult to develop an educational system without considering the motivational system involved in this system.…”
Section: Introductionmentioning
confidence: 99%
“…Media is one factor that determines teaching success because it helps students and teachers deliver the subject matter in connection with teaching objectives [5]. Of the many functions of media, one of the main functions of learning media is as an intermediary capable of conveying messages or information so that they can support and affect the quality of learning provided by educators, such as motivation to learn for students, encouragement to learn, and a sense of belonging.…”
Section: Multimedia-based Learning Media Learningmentioning
confidence: 99%
“…The most significant issues can be observed in table 2 where the processes related to the communication channel are displayed while showing the significant role of according to the type of channel or data input (view, speak, listen, touch, peer communication, etc ...): as well as the importance of interfaces and the type of device through which the test is delivered. http://www.i-jet.org What is most important is to ensure that the IT tools serve to guarantee that the test items really reflect the real life tasks, especially in terms of usability [25], interactivity [26], accessibility [27], user experience [28], acceptance [29] and multimedia [30], than can be assessed through the ad-hoc designed rubrics. The model presented above (figure 1) requires the use of online methodologies to access to part of the information learned and received online in the different test items, which includes digital content adapted for language testing [4].…”
Section: Conceptual Frameworkmentioning
confidence: 99%